1.90-1.88Ga arc magmatism of central Fennoscandia: geochemistry, U-Pb geochronology, Sm-Nd and Lu-Hf isotope systematics of plutonic-volcanic rocks from Southern Finland - J. Kara; M. Väisänen; Å Johansson; Y. Lahaye; H. O'Brien; O. Eklund (UNIV BARCELONA, 2025)
The earliest Svecofennian magmatism in southern Finland has been dated to 1.90-1.88Ga. As an example of this, the Orijarvi (ca. 1.89Ga) and Enklinge (ca. 1.88Ga) volcanic centres comprise bimodal plutonic batholiths surrounded by volcanic rocks of comparable ages and chemical compositions. The rock types range from gabbros to granites and indicate a subduction-related continental margin setting. The zircons from the Orijarvi granodiorite define an age of 1892 +/- 4Ma whereas the Enklinge granodiorite yields an age of 1882 +/- 6Ma. Several inherited ages of 2.25-1.95Ga as well as younger metamorphic ages of 1.86-1.80Ga were found in the Enklinge granodiorite. The initial ENd values of the mafic rocks from both locations fall in the range +1.1 to +2.9, whereas the felsic rocks exhibit initial sNd values of-0.4 to +1.2. The magmatic zircons from the Orijarvi and Enklinge granodiorites show average initial sHf values of-1.1 (at 1892Ma) and zero (at 1882Ma), respectively, both with a spread of about 7 s-units. The initial sHf values for the inherited zircons from Enklinge range from +3.5 to +7.6 with increasing age. The Sm-Nd data indicate that the mafic rocks were derived from a "mildly depleted" mantle source while the felsic rocks show some crustal contribution. Also, the variation in sHf values indicates minor mixing between mildly depleted mantle-derived magmas and crustal sources. U-Pb ages and Hf isotopes for inherited zircons from the Enklinge granodiorite suggest the presence of juvenile Svecofennian "proto-crust" at depth.